16.1: Negative‐Bias Photodegradation Mechanism in InGaZnO TFT. Issue 1 (1st July 2013) - Tsubuku, Masashi; Watanabe, Ryosuke; Ishihara, Noritaka; Kishida, Hideyuki; Takahashi, Masahiro; Yamazaki, Shunpei; Kanzaki, Yohsuke; Matsukizono, Hiroshi; Mori, Shigeyasu; Matsuo, Takuya
Abstract Recent studies have shown that IGZO are variously influenced by photoirradiation. In this study, by using measurement results of optical properties and calculation results, a relationship of defect levels in the IGZO films and the SiO2 films to negative‐bias photodegradation was examined, and the mechanism of the degradation was revealed.